Versatile Genetic Tool Box for the Crenarchaeote Sulfolobus acidocaldarius - Wagner, Michaela; van Wolferen, Marleen; Wagner, Alexander; Lassak, Kerstin; Meyer, Benjamin H.; Reimann, Julia; Albers, Sonja-Verena (Frontiers in Microbiology, 2012)
For reverse genetic approaches inactivation or selective modification of genes are required to elucidate their putative function. Sulfolobus acidocaldarius is a thermoacidophilic Crenarchaeon which grows optimally at 76 °C and pH 3. As many antibiotics do not withstand these conditions the development of a genetic system in this organism is dependent on auxotrophies. Therefore we constructed a pyrE deletion mutant of S. acidocaldarius wild type strain DSM639 missing 322 bp called MW001. Using this strain as the base, we describe here different methods using single as well as double crossover events to obtain markerless deletion mutants, tag genes genomically and ectopically integrate foreign DNA into MW001. These methods enable us to construct single, double and triple deletions strains that can still be complemented with the pRN1 based expression vector. Taken together we have developed a versatile and robust genetic tool box for the crenarchaeote Sulfolobus acidocaldarius that will promote the study of unknown gene functions in this organism and makes this organism a suitable host for synthetic biology approaches.